Family-Centered Measures of Access to Early Care and Education - Elizabeth E. Davis; Won Fy Lee; Aaron J. Sojourner (Institute of Labor Economics (IZA), 2018)
This study proposes new family-centered measures of access to early care and education (ECE) services with respect to quantity, cost, and quality and uses them to assess disparities in access across locations and socio-demographic groups in Minnesota. These measures are distance-based and use available geographic data to account for the fact that families can cross arbitrary administrative boundaries, such as census tract or ZIP code lines, and thus better reflect the real experiences of families than conventional area-based measures. Combining synthetic family locations simulated from Census demographic and geographic data and information on ECE provider locations, we calculate travel time between the locations of families with young children and ECE providers to measure families' access to providers of different types. The results yield a map of areas with low and high relative ECE access. The average family in Minnesota lives in a location where there are nearly two children for every nearby slot of licensed capacity, however, access to ECE supply varies considerably at the local level. The supply measure can also serve as a weight useful in computing family-centered measures of ECE quality and access costs, incorporating both prices and travel costs, to further characterize the local ECE market from the perspective of families. Improving measures of variation in families' access to ECE quantity, cost, and quality is valuable as policymakers consider expansions to public supports for early learning and ECE entrepreneurs decide where to invest.
Keywords: J13; R12; R53; H4; L84; 330; child care; spatial analysis; public facility location; services